ANTIOXIDANT EFFECT OF VITAMINS COMBINED A, C, AND E DOSE ON TYPE 2 DIABETIC PATIENTS - GOZIF MOHAMMED N OMAR; FADEL YOUSIF AL-ARABI; MANSOUR ABDULNABI H MEHDI; MADHUKAR M FAWADE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: This study is to investigate the effect of oral Vitamins combined (A, C, and E) with metformin on the levels of fasting blood sugar (FBS), postprandial blood sugar (PPBS), hemoglobin (HbA1c), total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) in Type 2 diabetic patients. Methods: A total of 32 patients with Type 2 diabetes were divided randomly into A and B groups, i.e., 16 per each group. Group A received metformin only twice a day while Group B received one tablet of Antox and metformin twice a day for 3 months. FBS, PPBS, HbA1c, TC, TG, LDL, and HDL were measured before and after the dose, and the results were analyzed statistically. Results: A significant decreases in FBS, PPBS, HbA1c, TC, TG, and LDL whereas results showed increasing significance in HDL level that seen in the patients of Group B which received Antox and metformin compared to the group which received metformin only. In conclusion, the results indicate that daily consumption of supplementary vitamins with metformin leads to improving blood glucose and lipids in patients with Type 2 diabetes and reducing the risk of complications. Hence, the dose can be used combined Vitamins A, C, and E with metformin in the treatment of Type 2 diabetes by maintaining good glycemic control.